Grasping the Situation: analyzing how situational dynamics shape agency - Heijmeskamp, Thijs (Frontiers in Psychology, 2024)
Despite the intimacy between situation and our agency, “situation” remains an ambiguous concept in theory. Even within the context of situated theories of cognition and agency that take the organism-environment system as central in their investigations, the notion of “situation” has been undertheorized. Yet whether affordances are relevant depends on the situation. Van Dijk and Rietveld argue that therefore we must understand the practical situation in which behavior occurs in order to understand how we respond to the affordances that the material and other people offer. Taking John Dewey’s notion of “situation” as the basis for investigation, I follow Shaun Gallagher's analysis of how we are not just part of a situation, but we understand what an action is only in relation to a situation. Situations act like a large-scale affordance, but this does not mean that affordances are inviting or soliciting as such. Because of the situational transactions with the environment that an agent has, the environment pushes and pulls the agent from and towards certain actions. This means that environments have expressive qualitative features that are non-subjective emotional qualities and social gestalts. I propose four overlapping but distinct features or axes of analysis of situations that can be identified and that can be analyzed in terms of how they shape our agency: complexity, determinedness, establishment of expectations, and restrictiveness. Situations can be more or less complex in a spatial, temporal, or layered way. They can also be more or less determined, meaning that the agent’s actions are more or less obvious. Third, they can be characterized as socially established, meaning that certain behavior is expected. Finally, situations are more or less restricted, denoting the number of activities available to an agent.